Doppler Ultrasound in the Diagnosis of Portal Vein Stenosis in Adult Living Donor Liver Transplant with Left Lobe Liver Grafts - Hsu, Hsien-Wen; Huang, Tung-Liang; Chen, Tai-Yi; Leung-Chit Tsang, Leo; Ou, Hsin-You; Yu, Chun-Yen; Cheng, Yu-Fan; M. Concejero, Allan; Chen, Chao-Long (Current Medical Imaging, 2017)
Objectives: Our aim was to identify ultrasound criteria that may be used to detect portal vein stenosis (PVS) in adult living donor liver transplantation (ALDLT) with left lobe grafts. Methods: 171 recipients underwent primary left lobe graft aldlt and routine liver doppler ultrasound (DUS) as protocol. Another 151 right lobe liver donors who underwent pre-transplant and 6- month follow-up post-hepatectomy dus were chosen as a control group. Results: 68.4% (117/171) of the portal vein (PV) anastomoses can be well-visualized and measured by DUS but could not be visualized in 31.6% (54/171). Discussion: The values of portal anastomotic mean time averaged velocity (TAV) and change in anastomotic/pre-anastomotic portal velocity (ΔTAV) were 51.5 and 31.3 cm/s, respectively, for significant stenosis in patients with visualized PV anastomoses. Whether the PV anastomosis can be visualized or not by dus, the increased umbilical portal vein width indicating possible narrowing of the PV anastomosis was >2 cm. Increased TAV and ΔTAV are useful features to diagnose PVS in ALDLT. Conclusion: Identifying dilatation of left portal vein umbilical portion helps detecting PVS when the narrowed anastomosis cannot be visualized.
Keywords: portal vein stenosis